Neons fashion LLP (A) : a small seller on Amazon marketplace - Mukherjee, Saral; Abhishek; Balasubramani, Soundarya (London : Indian Institute of Management, Ahmedabad, 2019)
This case provides details of how independent sellers are at the mercy of marketplace operators and ends with the need to review the choices of sales channels for different categories like fashion garments and fashion accessories and for the upcoming launch of kids' shoes.
Originally Published in Mukherjee, S., Abhishek., & Balasubramani, S. (2019). Neons Fashion LLP (A): A small seller on Amazon marketplace. IIMA/MAR0509(A). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Small business -- Case studies; Teleshopping -- Case studies; Sales -- Case studies